Pengamatan Pasang Surut Untuk Penentuan Datum Ketinggian di Pantai Desa Parak, Kecamatan Bonto Matene, Kabupaten Selayar, Provinsi Sulawesi Selatan - Indra Mutiara; Amir Hamzah Muhiddin (Hasanuddin University, 2016)
Height of a point on land is determined by the position of sea level Average ( Mean Sea Level) . This paper investigates the Bench Mark local elevation measurements to Mean Sea Level tidal observations for 15 days at the village of Parak , District Bonto Matene, Selayar Regency, South Sulawesi Province . The results of the analysis of tidal by using the Admiralty Methode shows that the value of Mean Sea Level in the study site is 119 cm, Spring Tide tidal current was 93.04 cm, and based on the value of Formzahl, the tides tipe on this beach is mixed tide prevailing semidiurnal. The measurement results indicate that the height of local Bench Mark to the Mean Sea Level is amounted to +1.927 m.